Uncovering transgenerational phenotypic variation in Parthenium hysterophorus populations in Israel - Sahar Malka; Assaf Distelfeld; Maor Matzrafi (Planta, 2026)
Main conclusion Invasive Parthenium hysterophorus achieves rapid colonization via phenological divergence and population-specific transgenerational plasticity, balancing maternal environmental effects with rigid developmental canalization to outperform native flora across diverse habitats. Abstract Parthenium hysterophorus L. is a highly aggressive invasive weed that has spread across more than 50 countries, causing severe agricultural, ecological, and public health problems. Understanding phenotypic variation among invasive populations is critical for predicting invasion dynamics and designing effective management strategies. This study investigated phenological variation and transgenerational plasticity among five P. hysterophorus populations in northern Israel over three years. We compared developmental traits (emergence, bolting, flowering, height, and biomass) between field-collected seeds and their progeny grown under controlled greenhouse conditions. Significant phenological differences were observed among the populations, with field populations exhibiting more uniform development. These disparities persisted through to final height and weight measurements. A detailed transgenerational analysis of two contrasting populations (Tirat Zvi and Ha'Hotrim) revealed population-specific patterns of developmental plasticity. The Tirat Zvi population, originating from an extremely arid environment and representing the earliest documented Israeli introduction, demonstrated significant transgenerational shifts in emergence timing and a 25% increase in biomass under controlled conditions, while maintaining conserved flowering timing. In contrast, the Ha'Hotrim population exhibited a limited transgenerational response, with significant changes only in bolting timing. These contrasting patterns suggest different adaptive strategies: environmental anticipation through maternal effects versus intrinsic developmental canalization. The pronounced phenological divergence among populations, despite their short geographic separation, supports the hypothesis of multiple independent introductions or rapid local adaptation, with important implications for managing this invasive species in diverse agricultural landscapes.

Structural diversity of Ym2, a gene conferring resistance against Wheat yellow mosaic virus - Wenjing Xu; Xiaoyi Xu; Kohei Mishina; Youko Oono; Shun Sakuma; Mohammad Pourkheirandish; Assaf Distelfeld; Xiaoxue Zeng; Xiaolu Wang; Baoqiang Li; Takao Komatsuda; Cheng Liu (Theoretical and Applied Genetics, 2026)

Nitrogen deficiency tolerance conferred by introgression of a QTL derived from wild emmer into bread wheat - Nikolai Govta; Andrii Fatiukha; Liubov Govta; Curtis Pozniak; Assaf Distelfeld; Tzion Fahima; Diane M. Beckles; Tamar Krugman (Theoretical and Applied Genetics, 2024)
Key message Genetic dissection of a QTL from wild emmer wheat, QGpc.huj.uh-5B.2, introgressed into bread wheat, identified candidate genes associated with tolerance to nitrogen deficiency, and potentially useful for improving nitrogen-use efficiency. Abstract Nitrogen (N) is an important macronutrient critical to wheat growth and development; its deficiency is one of the main factors causing reductions in grain yield and quality. N availability is significantly affected by drought or flooding, that are dependent on additional factors including soil type or duration and severity of stress. In a previous study, we identified a high grain protein content QTL ( QGpc.huj.uh-5B.2 ) derived from the 5B chromosome of wild emmer wheat, that showed a higher proportion of explained variation under water-stress conditions. We hypothesized that this QTL is associated with tolerance to N deficiency as a possible mechanism underlying the higher effect under stress. To validate this hypothesis, we introgressed the QTL into the elite bread wheat var. Ruta, and showed that under N-deficient field conditions the introgression IL99 had a 33% increase in GPC ( p < 0.05) compared to the recipient parent. Furthermore, evaluation of IL99 response to severe N deficiency (10% N) for 14 days, applied using a semi-hydroponic system under controlled conditions, confirmed its tolerance to N deficiency. Fine-mapping of the QTL resulted in 26 homozygous near-isogenic lines (BC 4 F 5 ) segregating to N-deficiency tolerance. The QTL was delimited from − 28.28 to − 1.29 Mb and included 13 candidate genes, most associated with N-stress response , N transport, and abiotic stress responses. These genes may improve N-use efficiency under severely N-deficient environments. Our study demonstrates the importance of WEW as a source of novel candidate genes for sustainable improvement in tolerance to N deficiency in wheat.

Correction to: Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Rapid evolution of α-gliadin gene family revealed by analyzing Gli-2 locus regions of wild emmer wheat - Naxin Huo; Tingting Zhu; Shengli Zhang; Toni Mohr; Ming-Cheng Luo; Jong-Yeol Lee; Assaf Distelfeld; Susan Altenbach; Yong Q. Gu (Functional & Integrative Genomics, 2019)

GNI-A1 mediates trade-off between grain number and grain weight in tetraploid wheat - Guy Golan; Idan Ayalon; Aviad Perry; Gil Zimran; Toluwanimi Ade-Ajayi; Assaf Mosquna; Assaf Distelfeld; Zvi Peleg (Theoretical and Applied Genetics, 2019)

Reassessment of the evolution of wheat chromosomes 4A, 5A, and 7B - Jan Dvorak; Le Wang; Tingting Zhu; Chad M. Jorgensen; Ming-Cheng Luo; Karin R. Deal; Yong Q. Gu; Bikram S. Gill; Assaf Distelfeld; Katrien M. Devos; Peng Qi; Patrick E. McGuire (Theoretical and Applied Genetics, 2018)

SNP-based pool genotyping and haplotype analysis accelerate fine-mapping of the wheat genomic region containing stripe rust resistance gene Yr26 - Jianhui Wu; Qingdong Zeng; Qilin Wang; Shengjie Liu; Shizhou Yu; Jingmei Mu; Shuo Huang; Hanan Sela; Assaf Distelfeld; Lili Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

QTLs for uniform grain dimensions and germination selected during wheat domestication are co-located on chromosome 4B - Moran Nave; Raz Avni; Batsheva Ben-Zvi; Iago Hale; Assaf Distelfeld (Theoretical and Applied Genetics, 2016)

Functional characterization of GPC-1 genes in hexaploid wheat - Raz Avni; Rongrong Zhao; Stephen Pearce; Yan Jun; Cristobal Uauy; Facundo Tabbita; Tzion Fahima; Ann Slade; Jorge Dubcovsky; Assaf Distelfeld (Planta, 2014)

Increased copy number at the HvFT1 locus is associated with accelerated flowering time in barley - Rebecca Nitcher; Assaf Distelfeld; ChorTee Tan; Liuling Yan; Jorge Dubcovsky (Molecular Genetics and Genomics, 2013)

Identification and characterization of a novel powdery mildew resistance gene PmG3M derived from wild emmer wheat, Triticum dicoccoides - Weilong Xie; Roi Ben-David; Bin Zeng; Assaf Distelfeld; Marion S. Röder; Amos Dinoor; Tzion Fahima (Theoretical and Applied Genetics, 2012)

Divergent functions of orthologous NAC transcription factors in wheat and rice - Assaf Distelfeld; Stephen P. Pearce; Raz Avni; Beatrice Scherer; Cristobal Uauy; Fernando Piston; Ann Slade; Rongrong Zhao; Jorge Dubcovsky (Plant Molecular Biology, 2012)

Characterization of the maintained vegetative phase deletions from diploid wheat and their effect on VRN2 and FT transcript levels - Assaf Distelfeld; Jorge Dubcovsky (Molecular Genetics and Genomics, 2010)

Vrn-D4 is a vernalization gene located on the centromeric region of chromosome 5D in hexaploid wheat - Tetsuya Yoshida; Hidetaka Nishida; Jie Zhu; Rebecca Nitcher; Assaf Distelfeld; Yukari Akashi; Kenji Kato; Jorge Dubcovsky (Theoretical and Applied Genetics, 2010)

Identification of a novel gene (Hsdr4) involved in water-stress tolerance in wild barley - Tatiana Suprunova; Tamar Krugman; Assaf Distelfeld; Tzion Fahima; Eviatar Nevo; Abraham Korol (Plant Molecular Biology, 2007)

High-temperature adult-plant (HTAP) stripe rust resistance gene Yr36 from Triticum turgidum ssp. dicoccoides is closely linked to the grain protein content locus Gpc-B1 - Cristobal Uauy; Juan Carlos Brevis; Xianming Chen; Imtiaz Khan; Lee Jackson; Oswaldo Chicaiza; Assaf Distelfeld; Tzion Fahima; Jorge Dubcovsky (Theoretical and Applied Genetics, 2005)

Microcolinearity between a 2-cM region encompassing the grain protein content locus Gpc-6B1 on wheat chromosome 6B and a 350-kb region on rice chromosome 2 - Assaf Distelfeld; Cristobal Uauy; Sofia Olmos; Ana R. Schlatter; Jorge Dubcovsky; Tzion Fahima (Functional & Integrative Genomics, 2004)